Electrochemical Window of l-Butyl-3-Methylimidazoliuiii Hexafluorophosphate - Mamat, Muhd Azimey (Universiti Teknologi PETRONAS, 2010)
Room-Temperature Ionic Liquids, RTILs are liquids that compose entirely of ions and exist in the liquid state at room temperature. l-Butyl-3-Methylimidazolium Hexafluorophosphate, (CsHis^FeP) or BMM-PF6 is one of RTILs which is used in a wide variety of applications due to its attractive physical-chemical properties such as having wide electrochemical window value. The electrochemical window of an ionic liquid is the voltage range between whichthe substance doesn't get oxidized or reduced. This range is important for the efficiency of an electrode. Out of this range water gets electrolyzed, spoiling the electrical energy that is intended for another electrochemical reaction. The objective of this project is to determine the electrochemical window of ionic liquid that is l-Butyl-3-Methylimidazolium Hexafluorophosphate. The electrochemical window is measured by the reduction of the cation and the oxidation of the anion. The electrochemical window value can be obtained by running linear sweep voltammetry experiment. The electrochemical window value obtained from the experiment is about 2.3 V. in